2018
DOI: 10.3389/fpsyt.2018.00085
|View full text |Cite
|
Sign up to set email alerts
|

Event-Related Potential Measures of Attention Capture in Adolescent Inpatients With Acute Suicidal Behavior

Abstract: Impaired executive functions, modulated by the frontal lobes, have been suggested to be associated with suicidal behavior. The present study examines one of these executive functions, attentional control, maintaining attention to the task-at-hand. A group of inpatient adolescents with acute suicidal behavior and healthy controls were studied using a passively presented auditory optimal paradigm. This “optimal” paradigm consisted of a series of frequently presented homogenous pure tone “standards” and different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 98 publications
(94 reference statements)
2
10
0
Order By: Relevance
“…They found participants with a history of suicide attempts exhibited deficits in detecting “the need for inhibitory control,” as indexed by a more positive change in the N2 response of the ERP. Larger P3a components in a passively-presented auditory ERP paradigm were found in another sample of adolescent inpatients with suicidal behavior [ 142 ]. Activated dorsolateral prefrontal cortex has been demonstrated in fMRI studies of youth that attempted to regulate their emotional responses to negative pictures [ 143 ] as well.…”
Section: Discussionmentioning
confidence: 99%
“…They found participants with a history of suicide attempts exhibited deficits in detecting “the need for inhibitory control,” as indexed by a more positive change in the N2 response of the ERP. Larger P3a components in a passively-presented auditory ERP paradigm were found in another sample of adolescent inpatients with suicidal behavior [ 142 ]. Activated dorsolateral prefrontal cortex has been demonstrated in fMRI studies of youth that attempted to regulate their emotional responses to negative pictures [ 143 ] as well.…”
Section: Discussionmentioning
confidence: 99%
“…This could result in a larger target-N2 but reduced target-P3b in this group. Tavakoli et al 27 observed that passive attention capture was enhanced in their suicidal group. It is therefore possible that the while the target-P3b may be reduced, the novel-P3 may be enhanced in the suicidal group.…”
Section: The Present Studymentioning
confidence: 95%
“…The sample size was deemed to be appropriate based on a power analysis of effect size, using group means and SDs observed in our previous study. 27 With this effect size, a sample of 10 participants per group was found to be adequate. When the effect size was reduced to approximate mean group differences found in other studies, a sample size of 14 was found to be adequate.…”
Section: Participantsmentioning
confidence: 97%
See 2 more Smart Citations